Empowering Local Human Resources in the Internationalization Process: A Qualitative Study of Coffee-Based MSMEs - Oktavianti, Indira; Sudarmiatin Sudarmiatin; Heri Pratikto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the empowerment of local human resources as a strategic asset in the internationalization process of MSMEs in Sumber Wandhe Wonosalam, Jombang, East Java. This study employs a qualitative case study approach to facilitate the investigation of complex research phenomena, evaluate various perspectives, identify contributing factors, and generate a broad overview. The study indicates that success in internationalization requires a combination of capabilities that can meet market needs, rather than a single capability. Business actors who are able to recognize opportunities for local human resource empowerment can optimize the export process. This enables the region and its residents to maintain generational training in innovative management to address the turnover of the younger generation. Ultimately, this study provides a foundation for further research on the dynamic capabilities required for MSMEs to thrive in international markets.